2005
DOI: 10.1111/j.1740-8261.2005.00011.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effect of Laparoscopic and Conventional Pyloric Surgery on Gastric Emptying in Dogs

Abstract: The effect of a laparoscopic approach and pyloric surgery on canine gastrointestinal activity, particularly gastric emptying time, is not well understood. The purpose of this study was to compare the effect of laparoscopic and conventional pyloric surgery, in Ramstedt pyloromyotomy and Heineke-Mikulicz pyloroplasty, on complete gastric emptying time in 20 clinically normal dogs. Dogs were divided into four groups of five animals: dogs with laparoscopic Ramstedt pyloromyotomy, conventional Ramstedt pyloromyotom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Future investigations should identify the ideal technique Our previous studies demonstrated that laparoscopic Finney pyloroplasty is technically more demanding than Heineke-Mikulicz pyloroplasty or Ramstedt pyloromyotomy [12,13], but allows for a greater increase in pyloric diameter [11]. As this report shows, mechanical suturing has markedly simplified the gastroduodenal anastomosis.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…Future investigations should identify the ideal technique Our previous studies demonstrated that laparoscopic Finney pyloroplasty is technically more demanding than Heineke-Mikulicz pyloroplasty or Ramstedt pyloromyotomy [12,13], but allows for a greater increase in pyloric diameter [11]. As this report shows, mechanical suturing has markedly simplified the gastroduodenal anastomosis.…”
Section: Discussionmentioning
confidence: 70%
“…As in our previous studies [12,13], we performed fluoroscopic and ultrasonographic studies to determine the efficacy of the laparoscopic procedures. In both groups, the gastric emptying time was increased after surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The posterior walls of the gastric and the duodenum portions were closed with a continuous seromuscular suture running through the inferior gastroduodenal angle to proceed onto the anterior wall of the gastroduodenostomy. Recent studies reported the feasibility of LFP in a canine model, which strongly suggests applicability to human gastrointestinal surgery since canine and human anatomy in this region is similar (17). Sánchez-Margallo et al evaluated the technical feasibility of LFP in six dogs and successfully completed all the operations laparoscopically and postoperative studies assessed the correct function of the anastomosis (18).…”
Section: Discussionmentioning
confidence: 99%